Sistem Penentuan Titik Pengambilan Sampah Berdasarkan Status Berlangganan Menggunakan Peta Digital - Vianaza; Imam Muslem; Riyadhul Fajri (Jurnal Ilmu Komputer Aceh, 2026)
This study aims to design and develop a digital map-based system for determining waste collection points based on the subscription status of customers. Waste collection services in many areas are still managed manually, making it difficult to monitor customer locations, payment status, and complaint handling efficiently. To address this problem, a web-based information system is proposed to integrate customer data, payment status, complaint management, and waste collection point visualization through digital mapping technology. The system was developed using web technologies with a database to store user data, customer locations, payment records, and service complaints. Customers are able to register, save their home location using digital maps, make service payments according to their subscription category, and submit complaints related to waste collection services. Meanwhile, administrators can manage customer data, assign collection officers, monitor payment status, and view the distribution of customer locations through a digital map interface. Waste collection officers are provided with access to view the map of customers assigned to them and respond to complaints submitted by customers. The system automatically updates customer status based on subscription and payment information stored in the database. As a result, the map visualization can dynamically display the status of each customer location using different indicators. The implementation of this system is expected to improve efficiency in monitoring waste collection services, assist officers in determining collection routes, and enhance the quality of waste management services in the community